Track and field throwing sports: Injuries and prevention - Meron, A.; Saint-Phard, D. (Current Sports Medicine Reports, 2017)
Throwing events in track and field are among the oldest sporting events in recorded history and include shot put, discus, hammer, and javelin. All throwing athletes use the kinetic chain to transfer energy from the lower extremities, through the pelvis, trunk, shoulder, arm, wrist, hand, and finally into the implement to generate maximum force. Throughout this sequential activation, mobilization, and stabilization of body segments, there is opportunity for breakdown in the chain, which can lead to injury. This review describes the biomechanics and kinetic chain components of each event and highlights injuries common among all throwers as well as injuries unique to each event. The cornerstone of prevention is practicing and competing with proper technique. It is important to understand the breadth of injuries that can affect these athletes to develop evidence based diagnosis, treatment, and prevention strategies.